(untitled) (Baltic Journal of Sport and Health Sciences, 2024)
Background: This study extends the current knowledge on muscle deoxygenation during arm and leg ergometry in preadolescent swimmers. We aimed to compare the deoxygenation of legs and arms muscles during maximal incremental legs and arms exercises on the cycle ergometer (CE) and arm crank ergometer (ACE) in preadolescent swimmers. Methods: Thirteen preadolescent swimmers (aged 12 ± 1 years) were enrolled in this study. They performed two maximal incremental legs and arms exercises to exhaustion on CE and on ACE. During both exercises, muscles oxygen saturation values (the changes of deoxygenated haemoglobin (Δ[HHb]) and [HHb] thresholds ([HHb] thresholds) of Biceps femoris, Vastus lateralis, Rectus femoris, Triceps brachii, Infraspinatus and Biceps brachii muscles were recorded using the near-infrared spectroscopy method (Moxy oxygen monitor). Results: During maximal incremental legs and arms exercises on CE and ACE Δ[HHb] and [HHb] thresholds did not diﬀer significantly between legs and arms exercises (p>0.05) and between separate muscles (p>0.05) as well. Conclusion: Deoxygenation of legs and arms muscles was similar during incremental exercises on CE and ACE in preadolescent swimmers. Keywords: muscles oxygenation, NIRS, upper and lower body exercise, graded exercise test Keywords: muscles oxygenation, NIRS, upper and lower body exercise, graded exercise test